PENGARUH KUALITAS PRODUK CITRA MEREK, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELI SEPADA MOTOR MATIC HONDA SCOOPY (STUDI PADA KONSUMEN DEALER MERPATI MOTOR KOTA PROBOLINGGO) - Daimatul Musyarofah; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to examine and analyze the effect of product quality on brand and motorcycle purchasing decision (Honda Scoopy matic) in Merpati Motor dealer in Probolinggo. The research used explanatory research and quantitative approach. The respondents in this research were 80 people. They are consumers in Merpati Motor dealer.The method used is descriptive data analysis. it used validity test, reability test, normality test, multikolinierity test, heterokedastisity test, multiple linier analysis test, f test, t test. The result of this study simoultaneously, each product quality variable, price perception, and brand name have some positive effect on purchasing decision. Partially, product quality variable have effect on purchasing decision. Then price perception did not have effect for purchasing decision on Merpati Dealer Motor.